Patient With ST-Elevation Myocardial Infarction and Right Bundle Branch Block Refusing Reperfusion Therapy: A Case Report - Rezkinanda, Alief; Akbar, Dzulfikri Aulia; Rosali, Wanda; Anwar, Sdjaiful (Syntax Corporation, 2025)
ST-Elevation Myocardial Infarction (STEMI) is an emergency condition requiring prompt reperfusion therapy through fibrinolytic treatment or primary percutaneous coronary intervention (PCI) depending on what is available for the patient. However, in certain situations, especially in rural areas, patients may not receive these therapies. This case report reviews the condition of a STEMI patient who refused to be referred to the district hospital that provides reperfusion therapy and instead received dual antiplatelet therapy (DAPT), beta-blockers, angiotensin receptor blockers, statins, calcium channel blockers, and other supportive medications without any reperfusion therapy.